Business Models: Why Business Models Matter? - Ogunmola , Eyitayo Ebietoni (Management Analytics and Social Insights, 2024)
Why do business models matter? This is a question that seems pertinent and must be answered before embarking on any business. It is quite essential because of the competitive nature of the business space. As a system that has many sub-systems, business models describe how the elements of a business fit and work together. Nonetheless, these elements do not factor in one critical dimension of performance, which is competition, which is the function of the business model. This study clarifies the concept of business model, which is key to the performance of every business. A business model can be identified as a framework or blueprint that a business follows to generate revenue from which profit is earned. It outlines how a company will create, deliver, and capture value for its customers and stakeholders. Since the business model has a perfect correlation with revenue and profit, it is key to the survival and effectiveness of the business. Business models are, at heart, stories that explain how enterprises work. Like a good story, a robust business model contains precisely delineated characters, plausible motivations, and a plot that turns on an insight about value. It answers certain questions: who is the customer? How does business make money? What underlying economic logic explains the delivery of value to customers at an appropriate cost? Every viable organization is built on a sound business model, but a business model is not a strategy, even though many people use the terms interchangeably.